Formalisasi Hukum Ekonomi Islam: Peluang danTantangan (Menyikapi UU No. 3 Tahun 2006) - Rusydi, M. (Al-Mawarid Jurnal Hukum Islam, 2007)
Islamic economic law constitute the pilot project of islamic law research. This is more significance since the birth of modern Syariâah financial institutions based on provision of contract law in the sphere of Islamic economic law (muamalat) and also the rapid development of moslem business need the legal status to be implemented to resolve when ever the despute of muamalat contract exist. The formalization of Islamic economic law today, by the enactment of UU No. 3 Tahun 2006 become the most outstanding and rapid development that outweighing what has been formulated before and gives the religious court the widermandate to resolve despute of muamalat contract. This clearly gives the advantage of Moslem society to comply with Syariâah provision in their daily business activity from one hand, and also gives a challenge to Moslem society to mature this legal status from another. This writing tries to comprehend the formalization of Islamic economic law due to new release of UU No. 3 Tahun 2006 and look it from both perspective: opportunity and challenge. Kata kunci: hukum, ekonomi, Islam, formalisasi, dan implikasi.